Mixed-Use Building Design Apartments And Commercial Building - Edward Shobari; Kemal Affandi; Nutrian Galupamudia (Jurnal Arsitektur Archicentre, 2022)
By 2020, the 2,444,160 projected population of Bandung will continue to grow, as the need for housing in Bandung City is increasing, but the land is available for restricted housing. Congestion is a problem that needs to be solved as well too. This traffic was caused by a sizable Bandung movement, especially with the movement intent to work at 60.55%. To solve this problem, mixed buildings can be an alternative solution. The mixed-use building contained a vertical dwelling that increased land efficiency, and there is also a diversity of functions that can reduce movement. By choosing new urbanism themes, the entire design aspect of the mixed-use building is linked to 10(ten) new urbanism principles, such as material, public space, circulation, and landscape.